臺灣與美國華語教材之文化內容比較分析－以《新版實用視聽華語》與Integrated Chinese為例 - 張金蘭(Ching-Lan Chang) (Jiao ke shu yan jiu, 2022)
Culture is an indispensable aspect of Chinese teaching. Therefore, this study had a twofold purpose: to identify the core categories of the cultural content of Chinese textbooks and to analyze the distribution of the cultural content of two textbook sets. Cultural content was divided into 5 main categories and 17 subcategories. The two textbook sets, Practical Audiovisual Chinese (which is used in Taiwan), and Integrated Chinese (which is used in the United States), were compared and analyzed using the comparative education research method and content analysis. The analyses revealed two results. One was the uneven distribution of the cultural content in the two textbook sets, demonstrating a focus on surface culture and neglecting deep culture; the proportion of cultural content generally increased. The second was that the emergence of cultural subcategories in the two textbook sets was mostly the same. However, the American textbooks included more diverse content. Three suggestions were developed from these